Achalasia like disorder of the oesophagus in von Recklinghausen's neurofibromatosis. Issue 11 (November 1987) - Foster, P N; Stewart, M; Lowe, J S; Atkinson, M
Abstract : The association of achalasia like disorder of the oesophagus with von Recklinghausen's neurofibromatosis to our knowledge not previously reported is described in a 56 year old man who also had bladder dysfunction. At necropsy the oesophageal myenteric plexus showed ganglion cell depletion with nerve fibre hyperplasia probably the result of Schwann cell hyperplasia. We suggest that the disturbances of oesophageal and bladder function were a consequence of involvement of the autonomic nervous system by neurofibromatosis.